Experiential Learning Method for 4-5 Years Old Children in Improving the Ability to Recognize Colors at TK Negeri Pembina East Pontianak - Susilawati (CV Media Inti Teknologi, 2024)
This study aims to determine the increase in the ability to recognize colors in children aged 4-5 years using the experimental method in learning at Pembina Pontianak Timur State Kindergarten. The research procedure used is Classroom Action Research (CAR) with two cycles. The data source for this study is the teacher and the data are interview result sheets, observations, documentation, and children's worksheets. The results of this study were obtained from learning planning by PAUD teachers to improve the ability to recognize colors using the experimental method including: formulating activity materials, plans for compiling learning materials, plans for learning approaches and methods, plans for learning tools and resources, and assessment of learning outcomes. The implementation of learning includes: carrying out pre-learning, carrying out openings, carrying out core activities, utilizing game materials, assessing the process, and closing learning. The results of children's achievements were in the Very Good Development (BSB) category using the experimental method with a rapid increase from Cycle I (30%) then increasing in Cycle II (83%).